Second language speaking anxiety among Malaysian postgraduate students at a faculty of education - Badrasawi, Kamal J I; Solihu, Abdulateef; Tunku Ahmad, Tunku Badariah (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh, 2019)
This study aims to examine the level of second Language speaking anxiety among school teachers enrolled in a master of education program at the International Islamic University Malaysia. It also aims to determine if there are significant differences in the mean scores of speaking anxiety due to selected variables, namely gender, school location and teaching subject. A convenience sample comprising two hundred and ninety teachers (n= 290) completed an adopted 12-item survey on language speaking anxiety (Nazir, et al. 2014). Rasch Measurement modeling for polytomous data, independent samples t-test and one-way ANOVA test were used to analyze the collected data. Overall, the participants did not show high level of speaking anxiety, (Mean -.89 logits). They were mostly worried about expressing themselves effectively in English (-.66 logits), making mistakes while speaking (-.31 logits) and lecturers’ response to their mistakes (-.38 logits). A statistically significant difference in the mean scores of speaking anxiety was found due to teaching subject variable. The participants should further work on how to face the factors leading to their speaking anxiety. Further qualitative and quantitative studies with larger samples are recommended.